Pemetaan Sebaran Serangan Nematoda Sista Kentang (Globodera spp.) Pada Areal Sertifikasi Benih Kentang Kecamatan Pangalengan – Jawa Barat - Deni Indrawan; Lia Amalia; Nunung Sondari (Fakultas Pertanian Universitas Winaya Mukti, 2021)
The experiment was carried out, from September to November 2017 in the potato certification area of Kec. Pangalengan-West Java and Horticultural Plants Laboratory Center for Supervision and Certification of Seeds for Food Crops and Horticulture (BPSBTPH) West Java Province, Jl. Ciganitri II Bojongsoang-Bandung. The purpose of the experiment was to determine what factors affect the potato cyst nematode population and to determine the distribution of potato cyst nematode (Globodera spp.) in the potato seed certification area in Pangalengan District – West Java. The experimental design used was the field observation method in the potato seed certification area in Pangalengan District and areas suspected of being attacked by NSK, by measuring altitude, land slope, soil pH and rainfall data related to surface runoff and sampling. soil for laboratory analysis which will then be compared with field data for analysis using the ArcGIS 10.2 program. The experimental results show no correlation, showing the relationship between the variables has a small correlation value so that the degree of closeness of the relationship between the variables of altitude, land slope, soil pH, rainfall less influential. The distribution of potato cyst nematode attack (globodera spp.) in potato seed certification areas was found in Sukamanah, Margamukti, and Tribaktimulya villages in Pangalengan District - West Java.